2012
DOI: 10.1021/jp305096y
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Ligand Transfer in ba3 Oxidase from Thermus thermophilus: Simultaneous FTIR Detection of Photolabile Heme a32+–CN and Transient CuB2+–CN Complexes

Abstract: FTIR and light-minus-dark FTIR spectroscopy have been employed to investigate the reaction of oxidized and fully reduced ba(3) oxidase with cyanide. The characterization of the structures of the bound CN(-) in the binuclear heme Fe-Cu(B) center is essential, given that a central issue in the function of ba(3) oxidase is the extent to which the partially reduced substrates interact with the two metals. In the reaction of oxidized ba(3) oxidase with cyanide the initially formed heme a(3)(3+)-C≡N-Cu(B)(2+) specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…that the Cu B 2+ environment and its associated His-ligands, including the cross-linked His-Tyr237, is very rigid and not subject to conformational transitions that are associated with protonation/deprotonation events of the Cu B 2+ ligands. 20 Similar conclusions were drawn in the case of the Cu B + -CO complex. 18 Therefore, the Cu B environment is inflexible in both oxidation states of the metal, and the environment of the binuclear center (pH/pD = 6-9) of ba 3 -oxidase does not alter the protonation state of the polar His residues and Tyr237, which are the Cu B ligands.…”
Section: Chemcommsupporting
confidence: 68%
See 1 more Smart Citation
“…that the Cu B 2+ environment and its associated His-ligands, including the cross-linked His-Tyr237, is very rigid and not subject to conformational transitions that are associated with protonation/deprotonation events of the Cu B 2+ ligands. 20 Similar conclusions were drawn in the case of the Cu B + -CO complex. 18 Therefore, the Cu B environment is inflexible in both oxidation states of the metal, and the environment of the binuclear center (pH/pD = 6-9) of ba 3 -oxidase does not alter the protonation state of the polar His residues and Tyr237, which are the Cu B ligands.…”
Section: Chemcommsupporting
confidence: 68%
“…16 Resonance Raman (RR) and time-resolved stepscan FTIR spectroscopies have been applied extensively to investigate the ligand dynamics in the binuclear center of ba 3 -oxidase and, in conjunction with permutations of 15 N-and 18 O-labeled nitric oxide, have indicated that the reaction of oxidized ba 3 with NO yields the heme Fe a3 -bound hyponitrite species. [18][19][20][21] Furthermore, a six-coordinate heme Fe a3 2+ -NO species has been detected in the reaction of ba 3 -oxidase with NO, and it was proposed that a hyponitrite (HONNO À ) bound to the heme Fe 3+ /Cu B + center was transiently formed under reducing conditions. 22 The time-resolved step-scan FTIR experiments demonstrated a much lower affinity of Cu B + for NO than that for CO. 22 In light of the recent reports on nitrite reductase activity of cytochrome c oxidases 1,4 and the hypothesis of common evolution of aerobic respiration and denitrification, in this work, we have utilized optical absorption and RR spectroscopies to investigate the interactions of nitrite with the binuclear heme-copper center of ba 3 -oxidase.…”
mentioning
confidence: 99%
“…Cytochrome ba 3 oxidase has a high oxygen affinity, expressed under elevated temperatures T ¼ 47-85 C and limited oxygen supply with unusual ligand binding properties of Cu B . 29 Complete understanding of the thermodynamic and kinetic characterization of functional and physiologically relevant ligands, electron and proton pathways is a necessity for the elucidation of the adaptation mechanism. The behaviour of the cofactors involved in the peculiar ligand binding and electron transfer properties observed at room temperature with those at high and low temperatures will lead to a total decoding of the adaption mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the crystal structure cytochrome ba 3 from Thermus thermophilus contains a homodinuclear copper center (Cu A ), a low-spin heme b , and a heme a 3 -Cu B center [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. Cytochrome ba 3 catalyzes the reductions of oxygen (O 2 ) to water (H 2 O) and of nitric oxide (NO) to nitrous oxide (N 2 O), as well and the oxidation of carbon monoxide (CO) to carbon dioxide (CO 2 ) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24]. The photolyzed ba 3 -CO species is an excellent model for time-resolved spectroscopic studies [7,8,9,13,15,18,24].…”
Section: Introductionmentioning
confidence: 99%